Role of gastrointestinal endoscopy in the screening of digestive tract cancers in Europe: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Săftoiu, Adrian; Hassan, Cesare; Areia, Miguel; Bhutani, Manoop S.; Bisschops, Raf; Bories, Erwan; Cazacu, Irina M.; Dekker, Evelien; Deprez, Pierre H.; Pereira, Stephen P.; Senore, Carlo; Capocaccia, Riccardo; Antonelli, Giulio; van Hooft, Jeanin; Messmann, Helmut; Siersema, Peter D.; Dinis-Ribeiro, Mario; Ponchon, Thierry (Endoscopy, 2020)
In Europe at present, but also in 2040, 1 in 3 cancer-related deaths are expected to be caused by digestive cancers. Endoscopic technologies enable diagnosis, with relatively low invasiveness, of precancerous conditions and early cancers, thereby improving patient survival. Overall, endoscopy capacity must be adjusted to facilitate both effective screening programs and rigorous control of the quality assurance and surveillance systems required.1 For average-risk populations, ESGE recommends the implementation of organized population-based screening programs for colorectal cancer, based on fecal immunochemical testing (FIT), targeting individuals, irrespective of gender, aged between 50 and 75 years. Depending on local factors, namely the adherence of the target population and availability of endoscopy services, primary screening by colonoscopy or sigmoidoscopy may also be recommendable. 2 In high-risk populations, endoscopic screening for gastric cancer should be considered for individuals aged more than 40 years. Its use in countries/regions with intermediate risk may be considered on the basis of local settings and availability of endoscopic resources.3 For esophageal and pancreatic cancer, endoscopic screening may be considered only in high-risk individuals:– For squamous cell carcinoma, in those with a personal history of head/neck cancer, achalasia, or previous caustic injury; – For Barrett’s esophagus (BE)-associated adenocarcinoma, in those with long-standing gastroesophageal reflux disease symptoms (i. e., > 5 years) and multiple risk factors (age ≥ 50 years, white race, male sex, obesity, first-degree relative with BE or esophageal adenocarcinoma [EAC]). – For pancreatic cancer screening, endoscopic ultrasound may be used in selected high-risk patients such as those with a strong family history and/or genetic susceptibility.